Financial Distress, Capital Structure, Cash Flow, and Production Capacity on the Value of Transportation Sub-Sector Companies - Kurniasari, Zenita; Rachmawati, Desiana; Agustin, Alifiya Nur; Kinanti, Chika Amelia (Dinasti Publisher, 2025)
The author conducted research to prove the hypothesis and analyze the influence of financial distress, capital structure, cashflow, and operating capacity on firm value. A quantitative approach was used using secondary data in the form of financial reports of transportation sub-sector companies listed on the Indonesia Stock Exchange. There were 60 observations with panel data, namely cross-sectional data from 12 transportation sub-sector companies reviewed in time series for 5 reporting periods, namely 2019-2023. The analysis used a multiple linear regression model with four independent variables (DIST, STRC, CF, OPR) and one dependent variable (FV). The data testing results found that DIST and STRC individually had a significant negative effect on FV. Furthermore, CF and OPR individually had a positive and significant effect on FV. Kesulitan keuangan can be an indicator of a company approaching bankruptcy and reduce investor confidence, which assesses the company as less profitable. A lower STRC ratio indicates better capital adequacy, which can increase investor confidence and assess the company as more profitable. Good CF and OPR conditions can increase FV because investors assess the company's liquidity and operational performance as being quite healthy.